Lack of Cell Cycle Inhibitor p21 and Low CD4+ T Cell Suppression in Newborns After Exposure to IFN-β - Jans, Jop; Unger, Wendy W.; Raeven, Elisabeth A. M.; Simonetti, Elles R.; Eleveld, Marc J.; de Groot, Ronald; de Jonge, Marien I.; Ferwerda, Gerben (Frontiers in immunology, 2021)
Type I IFNs, such as interferon alpha and interferon beta, are key regulators of the adaptive immune response during infectious diseases. Type I IFNs are induced upon infection, bind interferon α/β receptors on T-cells and activate intracellular pathways. The activating and inhibitory consequences of type I IFN-signaling are determined by cell type and cellular environment. The neonatal immune system is associated with increased vulnerability to infectious diseases which could partly be explained by an immature CD4 + T-cell compartment. Here, we show low IFN-β-mediated inhibition of CD4 + T-cell proliferation, phosphorylation of retinoblastoma protein and cytokine production in human newborns compared to adults. In addition, both naïve and total newborn CD4 + T-cells are unable to induce the cell-cycle inhibitor p21 upon exposure to IFN-β in contrast to adults. The distinct IFN-β-signaling in newborns provides novel insights into T cell functionality and regulation of T cell-dependent inflammation during early life immune responses.